2022
DOI: 10.1145/3505637
|View full text |Cite
|
Sign up to set email alerts
|

PyMatching: A Python Package for Decoding Quantum Codes with Minimum-Weight Perfect Matching

Abstract: This paper introduces PyMatching, a fast open-source Python package for decoding quantum error-correcting codes with the minimum-weight perfect matching (MWPM) algorithm. PyMatching includes the standard MWPM decoder as well as a variant, which we call local matching , that restricts each syndrome defect to be matched to another defect within a local neighbourhood. The decoding performance of local matching is almost identical to that of the standard MWPM decoder in practice, while redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Additionally, for decoding, we have used the PyMatching library [43], which implements the MWPM algorithm [27] to calculate the data qubits that need correction from a provided error syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for decoding, we have used the PyMatching library [43], which implements the MWPM algorithm [27] to calculate the data qubits that need correction from a provided error syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one could also bring ideas from UF decoders into the blossom algorithm to improve the latter's speed. For example, we have recently shown that instead of the syndrome graph, MWPM decoders can be made faster [22] by adopting the decoding graph used by UF decoders, which has also been indepen-dently discovered by Higgott and Gidney [23]. two error patterns, E 1 and E 2 , we define their sum as…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper we use a slightly modified lookup table decoder that is foolproof and fast. The proposed code is not a Calderbank-Shor-Steane code [8,11], thus we cannot analyze X and Z errors separately and use common minimum-weight perfect matching decoding algorithm [35,36]. However, there are other alternative promising decoding methods, that for example use neural network approach [30,37] or approximate matrix product state simulations [38], but they are usually time and memory consuming.…”
Section: Discussionmentioning
confidence: 99%